Biorreator da 5’-deoxi-5’-metiltioadenosina fosforilase: do desenvolvimento a aplicação em ensaios de afinidade - Rodrigues, Juliana Gomes (2023)
5'-deoxy-5'-methylthioadenosine phosphorylase (MTAP) is an enzyme present in many organisms, including the parasite Schistosoma mansoni, which causes schistosomiasis. The classic MTAP enzymatic assay is coupled to the reaction of another enzyme and indirectly measures adenine formation. The main disadvantage of these coupled assays is that any interference in the activity of the second enzyme directly affects the activity of the main enzyme. Therefore, an LC-UV chromatographic method was developed and validated to directly monitor the catalytic activity of MTAP in the conversion of adenosine substrate into adenine. The enzyme was covalently linked to the surface of magnetic particles, to obtain a bioreactor that was applied in the screening of molecules in extracts of natural products, through the affinity selection mass spectrometry technique. For this purpose, the test known as ligand fishing was developed and applied to prospect for ligands in methanolic extracts of the marine sponge Topsentia ophiraphidites and the stem bark of Aspidosperma macrocarpon. Among the Feature-Based Molecular Networking, the MZmine software was used for the processing and interpretation of the fingerprint chromatograms obtained by LC-HRMS of the assay. Subsequently, the Ichthus software was used to align the molecular characteristics, calculate the affinity ratio and thus distinguish the selective ligands for the enzyme. The binders were inspected manually through analyzes in the chemical profile of the extracts of natural products and in the blank sample, to discard the artifacts. After selection, the ligands were submitted to the dereplication process with the support of platforms such as GNPS and databases such as Dictionary of Natural Products, KNApSAcK Core System, MassBank, PubChem, SciFinder, LIPID MAPS and HMDB.